2017
DOI: 10.1177/1464420716680499
|View full text |Cite
|
Sign up to set email alerts
|

Reliability-based high cycle fatigue design approach of parabolic leaf spring

Abstract: It is well established that the fatigue phenomenon of metallic structures such as leaf springs presents a random behavior, which is influenced by a probabilistic effect of many factors. This paper presents a probabilistic design approach to predict the high cycle fatigue behavior of a single asymmetric parabolic leaf spring. The suggested approach is used to assess the fatigue reliability of a single asymmetric parabolic leaf spring with uncertainties associated with its design parameters. This approach is bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…As an essential part of the automobile, the reliability of leaf spring performance and quality directly affects its driving safety. Furthermore, leaf springs are subjected to great alternating loads during driving [4][5][6]. Therefore, automobile manufacturers have high requirements for the high surface quality of the leaf springs.…”
Section: Introductionmentioning
confidence: 99%
“…As an essential part of the automobile, the reliability of leaf spring performance and quality directly affects its driving safety. Furthermore, leaf springs are subjected to great alternating loads during driving [4][5][6]. Therefore, automobile manufacturers have high requirements for the high surface quality of the leaf springs.…”
Section: Introductionmentioning
confidence: 99%
“…To predict the fatigue failure of a parabolic leaf spring, the finite element analysis (FEA) is widely used to simulate the applied stress distribution and fatigue behaviour in the design stage. [14][15][16][17][18][19][20] Nevertheless, the deterministic and probabilistic optimisation of leaf spring design parameters, which need a large number of stress model calls, [21][22][23] involve a considerable computational effort by using a FEM of parabolic leaf spring (PLS). Therefore, it is very important to use a simple and precise model to carry out the applied stress distribution.…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the fatigue resistance according to the Gerber criterion, the probabilistic approach was developed using the ‘strength-load’ method and Monte Carlo simulations. 6…”
Section: Introductionmentioning
confidence: 99%
“…To estimate the fatigue resistance according to the Gerber criterion, the probabilistic approach was developed using the 'strength-load' method and Monte Carlo simulations. 6 The influence of the environmental media on fatigue life manifested in the variation of fatigue life with applied stress, grain size, inclusion size and material yield stress was explained. It was concluded that fatigue life decreases with the applied loading and inclusion size, whereas it increases with the material yield stress.…”
Section: Introductionmentioning
confidence: 99%